Environmental Concern and It`s Relationship to Values And The Awareness of Environmental Consequences at Students of University Stage (Damascus University Journal of educational and Psychologyical sciences, 2024)
The research aimed to investigate the relationships between environmental concern, values and the awareness of environmental  Adverse consequences at The sample consisted of (119) male and female  from the university stage students which responded to environmental concern(EC) scale (schultz,2001) with three factors (Egoistic Environmental Concern, Altruistic Environmental Concern And Biospheric Environmental Concern), Schwartz Values Survey(1992), Awareness Of Environmental Consequences (Ryan& Spash,2008) With Three Factors: Awareness Of Consequences To Oneself(ACego),  Awareness Of Consequences To Other Humans (AChum) and Awareness Of Consequences To Biosphere (ACbio), Environmental Problems Questionnaire Developed By  The Researcher, And The Inclusion Of Nature In Self Scale(Ins) by Schultz(2001). The Most Important Results Were: The(Egoistic EC, Altruistic EC, Biospheric EC) Levels for The Sample Were Moderate such that of the (ACego) and (ACbio), but (AChum), Which Was High.  And Each Of The Security And Power Value Types, (AChum) and (ACbio) Were Predictors Of Egoistic EC.  The Security And Power Value Types Were Predictors Of Altruistic EC And It Could Be Predicted Of Biospheric EC From Universalism And Tradition Value Types. Egoistic And Altruistic EC Were Positively Correlated To Four Values Dimensions: Self-Transcendence, Self-Enhancement, The Openness To Change And Conservation. And So That Was Biospheric EC Which Correlated To All Of Them Except Of Self-Enhancement. There Wasn`t Gender Differences About EC and AC factors.  Finally Those of Higher Level Of Exposure To Environmental Objects And Issues Were More Biospheric EC, (AChum) and (ACbio).
Keywords: Environmental Concern(EC; - Egoistic EC; Altruistic EC; Biospheric EC; The Awareness Of Consequences (AC); AC To Ego; AC To Humans; AC To Biosphere; Security Values Type; Power Values Type; - Universalism Values Type; Tradition Values Type; Self-Transcendence Values; Self-Enhancement; The Openness To Change; - Conservation Gender.